2006
DOI: 10.1101/gad.374006
|View full text |Cite
|
Sign up to set email alerts
|

ASPP2 is a haploinsufficient tumor suppressor that cooperates with p53 to suppress tumor growth

Abstract: ASPP2 stimulates the apoptotic function of the p53 family in vivo. We show here that ASPP2 −/− pups died before weaning. This postnatal lethality was significantly enhanced in p53 +/− background and both deletions are synthetic lethal. ASPP2 +/− mice developed spontaneous tumors. The tumor onset was accelerated by ␥-irradiation or in p53 +/− background. Tumors derived from ASPP2 +/− mice retained wild-type ASPP2 allele even though some of them lost p53. These provide the first genetic evidence that ASPP2 is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
97
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 98 publications
(106 citation statements)
references
References 20 publications
6
97
3
Order By: Relevance
“…The binding of ASPP family proteins selectively modulate the apoptosis function of p53 family proteins and finally decide cell fortune between life and death (Figure 4). Furthermore, a mouse model study by Vives et al (2006) and other invitro and invivo studies by Samuels-Lev et al (2001), Bergamaschi et al (2003) and Lettre et al (2004) sustaining that ASPP1 and ASPP2 act as tumor suppressors, at the same time, iASPP as an oncogene.…”
Section: Aspps: Arbiters Of Cell Survival and Apoptosismentioning
confidence: 89%
“…The binding of ASPP family proteins selectively modulate the apoptosis function of p53 family proteins and finally decide cell fortune between life and death (Figure 4). Furthermore, a mouse model study by Vives et al (2006) and other invitro and invivo studies by Samuels-Lev et al (2001), Bergamaschi et al (2003) and Lettre et al (2004) sustaining that ASPP1 and ASPP2 act as tumor suppressors, at the same time, iASPP as an oncogene.…”
Section: Aspps: Arbiters Of Cell Survival and Apoptosismentioning
confidence: 89%
“…Mouse embryonic fibroblasts (MEFs) are a well-established experimental system used to study oncogene-induced senescence. To investigate whether ASPP2 has a role in mediating Ras oncogene-induced senescence, MEFs were generated from ASPP2 ( þ / þ ) and ASPP2 (D3/D3) embryos, where exon 3 of the murine ASPP2 gene was deleted as previously described, 19 and infected with oncogenic H-RasV12. As expected, the expression of oncogenic H-RasV12-induced senescence in ASPP2 ( þ / þ ) MEFs was detected by the presence of the senescence marker senescence-associated b-galactosidase (SA-b-Gal), but not in ASPP2 (D3/D3) MEFs (Figure 1a and b).…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, heterozygous mice of ASPP2 (D3/ þ ) and ASPP2 (D10À17/ þ ) are both prone to developing spontaneous tumors, establishing ASPP2 as a new haploinsufficient tumor suppressor. 19,20 ASPP2 expression is frequently downregulated in human tumors, and reduced ASPP2 expression is tightly associated with patients' poor prognosis. 21,22 As ASPP2 can bind other cellular proteins including p65 reticuloendotheliosis viral oncogene homolog A, B-cell lymphoma 2, protein phosphatase 1, YES-associated protein, adenomatous polyposis coli-like and amyloid-b precursor protein binding protein 1, [23][24][25][26][27][28] it is possible that ASPP2 suppresses tumor growth in ways other than promoting p53-mediated apoptosis.…”
mentioning
confidence: 99%
“…Existing studies have suggested that ASPP2 plays a central role in the regulation of apoptosis and cell growth. The most compelling evidence comes from the ASPP2 knockout mouse study (Vives et al, 2006). The group examined the role of ASPP2 in tumorigenesis and its relationship with p53 tumour suppression in homozygous or heterozygous mice lacking ASPP2 or ASPP2 and p53 alleles.…”
Section: Iaspp Is a Proto-oncogene Whereas Aspp1 And Aspp2 Are Tumourmentioning
confidence: 99%